Mouse B cells engineered to express an anti-HPV antibody elicit anti-tumor T cell responses - Michal Guberman Bracha; Michal Guberman Bracha; Guy Biber; Natalie Zelikson; Sharon Shavit; Roy Avraham; Yaron Vagima; Yaron Vagima; Débora Rosa Bublik; Yael Katz; Adi Barzel; Leah Natasha Klapper; et al. (Frontiers in Immunology)
Transplantation of engineered B cells has demonstrated efficacy in HIV disease models. B cell engineering may also be utilized for the treatment of cancer. Recent studies have highlighted that B cell activity is associated with favorable clinical outcomes in oncology. In mice, polyclonal B cells have been shown to elicit anti-cancer responses. As a potential novel cell therapy, we demonstrate that engineering B cells to target a tumor-associated antigen enhances polyclonal anti-tumor responses. We observe that engineered B cells expressing an anti-HPV B cell receptor internalize the antigen, enabling subsequent activation of oncoantigen-specific T cells. Secreted antibodies from engineered B cells form immune complexes, which are taken up by antigen-presenting cells to further promote T cell activation. Engineered B cells hold promise as novel, multi-modal cell therapies and open new avenues in solid tumor targeting.